Exploring the therapeutic potential of different sources of mesenchymal stem cells: a novel approach to combat burn wound infections - Aliniay-Sharafshadehi, Shahrzad; Yousefi, Mohammad Hasan; Ghodratie, Mohammad; Kashfi, Mojtaba; Afkhami, Hamed; Ghoreyshiamiri, Seyed Mehdi (Frontiers in Microbiology, 2024)
The most prevalent and harmful injuries are burns, which are still a major global health problem. Burn injuries can cause issues because they boost the inflammatory and metabolic response, which can cause organ malfunction and systemic failure. On the other hand, a burn wound infection creates an environment that is conducive to the growth of bacteria and might put the patient at risk for sepsis. In addition, scarring is unavoidable, and this results in patients having functional and cosmetic issues. Wound healing is an amazing phenomenon with a complex mechanism that deals with different types of cells and biomolecules. Cell therapy using stem cells is one of the most challenging treatment methods that accelerates the healing of burn wounds. Since 2000, the use of mesenchymal stem cells (MSCs) in regenerative medicine and wound healing has increased. They can be extracted from various tissues, such as bone marrow, fat, the umbilical cord, and the amniotic membrane. According to studies, stem cell therapy for burn wounds increases angiogenesis, has anti-inflammatory properties, slows the progression of fibrosis, and has an excellent ability to differentiate and regenerate damaged tissue. Figuring out the main preclinical and clinical problems that stop people from using MSCs and then suggesting the right ways to improve therapy could help show the benefits of MSCs and move stem cell-based therapy forward. This review’s objective was to assess mesenchymal stem cell therapy’s contribution to the promotion of burn wound healing.